Preparation of SiO2 coated carbon fibers and its interfacial properties with cement paste matrix - Geng, Yanan; Ren, Qiang; Yang, Zengmin; He, Dan; Wu, Zhiqiang; Cai, Jingxuan; Zhang, Chunmei; Cheng, Xiaowei (Frontiers in Materials, 2023)
As a porous brittle material, oil well cement in oil and gas well cementing is difficult to bear complex loads, which can easily lead to the failure of the mechanical integrity of cement sheath. In this paper, SiO2 coating-CF toughening material was obtained by SiO2 modified carbon fibers (CFs) surface. In addition, the mechanical properties and mechanism of SiO2 coating-CF cement stone were discussed. The obtained results showed that the mechanical properties of SiO2 coating-CF cement stone are significantly improved. After 14 days of curing, the compressive strength can reach 32.98 MPa and the tensile strength is increased by 162%. The CF after adding SiO2 surface film improves the adhesion between the interface and the fiber by forming chemical bonds at the bonding surface with the cement stone, so as to improve the CF reinforced cement stone.